Activating entrepreneurial learning processes for transforming university students' idea into entrepreneurial practices. Issue 3 (2nd May 2017) - Secundo, Giustina; Del Vecchio, Pasquale; Schiuma, Giovanni; Passiante, Giuseppina
Abstract : Purpose: The purpose of this paper is to explore how collaborative entrepreneurial learning (EL) processes between entrepreneurs and university students can enhance the entrepreneurial practices in the context of knowledge-intensive enterprises. These learning processes represent a valuable source for entrepreneurship development in incumbent enterprises in the forms of innovative products, services, processes or organizational renewal. Design/methodology/approach: An extreme case study is the project "Mimprendo" (www.mimprendo.it ), an initiative promoted by the Italian Conference of the University Colleges and the Italian Association of Young Entrepreneurs in collaboration with Italian universities. This is analyzed in the period 2009-2015, during which seven editions were developed. Findings: A framework is presented based on collaborative EL processes to perform relevant entrepreneurial projects in knowledge-intensive enterprises. The framework provides a coherent and systematic approach to generate, select and implement entrepreneurial practices in incumbent companies starting from a project competition involving creative students and innovative entrepreneurs. EL processes in the community composed of entrepreneurs, experts and university students are grouped into the entrepreneurial phases of inspiration, exploration, exploitation, acceleration and growth, and include the learning processes of "intuition and sensing, " "contamination, " "experiential and contextual learning, " "experimenting and acting" and finally "thinking and reflecting." Research limitations/implications: Implications for research can be identified according to many perspectives to deepen the centrality of the learning process in the research on knowledge-intensive entrepreneurship. Practical implications: The framework results to be a promising approach to diffuse an entrepreneurial culture both in incumbent enterprises and in university students through a synergic collaboration among industry, university and institution. Practical implications could be derived for enterprise, students and educators involved in the design of innovative learning initiatives to sustain the development of an entrepreneurial mind-set. Originality/value: The framework contributes to extending an emerging research area exploring entrepreneurship as a never-ending dynamic learning process. The involvement of brilliant university students in activating EL process with entrepreneurs in incumbent enterprises represents a novel aspect in the field of entrepreneurship and innovation.